Intersectionality of Cultural Identities in Health Psychology: Key Recommendations for Working With African-Caribbean Immigrant Women - Dixon, Sandra (Frontiers in Sociology, 2019)
While the field of health psychology has progressed over the years, much work still needs to be done when considering immigrants’ health care and well-being. Particularly, for African-Caribbean immigrants, the intersectionality of their cultural identities in the health care system require much attention moving forward. Therefore, this article is particularly relevant for Canada’s multicultural society; it describes cultural identity reconstruction within health psychology as a common issue for diverse groups, particularly African-Caribbean immigrant women. The article speaks to the holistic worldview that is required in a paradigm shift which engages a pluralistic society that is Canada. The author presents a key cultural identity model and assessment tool that should be integrated into the health care system to ensure culturally-sensitive and inclusive care for immigrants, especially women. As is argued in the article, contemporary research, advocacy and social movements speak to invoking alternative ways to complement the prevailing downstream approach to health psychology. In a growing multicultural society that should strive on honouring and respecting the pluralistic cultural worldviews of all people in the health care system, many immigrant women struggle to cope with the social determinants of health post-migration. Their concerns are often pushed to the margins of health care services, with several individuals relying on their faith for coping strategies. This article concludes with culturally-informed and socially-just recommendations for health care professionals working with immigrant populations, particularly African Caribbean immigrant women.